System of centers, the city of Belgrade and territorial organization of Serbia - Tošić, Branka (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2009)
This paper presents the basic characteristics of the systems of settlements and centers in Serbia. A forceful process of industrialization in the second half of the 20th century caused intensive urbanization which resulted in increasing of the number of urban settlements as well as their size, with prominent supremacy of the capital city, Belgrade. The system of centers in Serbia is represented by the hierarchy of urban centers with their spatial and functional areas as determined by the National spatial plan (1996). Territorial organization of the state is partially completed and defined on a macro-regional and local levels.
Keywords: Belgrade; Beograd; mesta; Serbia; Srbija; urbana geografija; urbanizacija